2016
DOI: 10.1002/suco.201400119
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical method for calculating the compressive arch capacity of RC beams against progressive collapse

Abstract: Compressive arch action is one of the main resistance mechanisms against progressive collapse in reinforced concrete (RC) buildings. Hence, many studies have investigated the development of arching action in RC beams and frames but less attention has been paid to calculating the corresponding enhancement in structural capacity. In the present study, a theoretical method is introduced in order to calculate the arching capacity of RC beams and also to obtain a quantitative assessment regarding structural robustn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Subsequently, the beam elongates under the increment of the applied loads, however, the restraint by other members leads to the occurrence of compression arch action in the beam-column assemblage. The arching action in addition to the beam axial forces are shown in Fig.1 [19], where the interior column consumes its bearing capability. Compression arch action mechanism in the beam-column assemblages is associated with axial compression forces.…”
Section: Assumptionsmentioning
confidence: 99%
“…Subsequently, the beam elongates under the increment of the applied loads, however, the restraint by other members leads to the occurrence of compression arch action in the beam-column assemblage. The arching action in addition to the beam axial forces are shown in Fig.1 [19], where the interior column consumes its bearing capability. Compression arch action mechanism in the beam-column assemblages is associated with axial compression forces.…”
Section: Assumptionsmentioning
confidence: 99%
“…Ultimate membrane capacity of one way slabs could be calculated based on the arching deformation theory (Rankin and Long, 1997). This concept is developed previously for obtaining the arching capacity of RC beams (Abbasnia and Mohajeri Nav, 2016). The mentioned procedure is utilized here in order to calculate the ultimate vertical load corresponding to the arching capacity of a RC sub-assemblage ( P B )…”
Section: Concept Of the Theoretical Modelmentioning
confidence: 99%
“…The numerical analysis carried out by Qi et al [16] to determine the dynamical response of CRC exposed to blast loading, the results indicated that the zone near the explosion has large local deformations with great damaged. Based on a theoretical study, Abbasnia and Nav [17] presented the procedure to estimate the structural robustness and also the arching capacity of beams. Additionally, through activating three-dimensional finite element approach of an actual existing deck-type reinforced concrete arch bridge, Farahani and Maalek [18] referred that the influences of the vertical component of ground motion must be included in the analysis of such construction.…”
Section: Introductionmentioning
confidence: 99%